A reasonable faith the case for Christianity in a secular world - Campolo, Anthony (Milton Keynes, UK Word, 1986)
Includes bibliographical references.
First published in the US in 1983 as "A reasonable faith : responding to secularism".
Keywords: Secularism -- religious aspects -- Christianity